Speech Technology in the University Area - Rangel Arenas, Adriana María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Man and technology is a manifestation that has been merged paradigm for several researchers in evolutionary Ser show over time. However, in some scenarios, this merger manifests as a self-destructive union in which the Self undermines the potential of technology decreasing its ability to develop a discourse that allows in - field case we significantly university - manage the process training. This research aims to identify the situation of break between discourse and technology generat-ed by the students of the University of Zulia, in the context of management knowledge and metacognition, which will then in turn develop training processes in which knowledge and technology are robust and significant elements. The research has been developed under the qualitative approach to the systematization of experiences. From the results we can state that generated the University Institutions should not just be guarantors of specific training for professionals, but at the same time provide the necessary tools to ensure quality, competitiveness and productivity during this learning process.